Analisis Faktor Pemicu Sustainability UMKM Pasca Pandemi Covid-19 - Rusyida, Wilda Yulia; Rifaldi, M. Raikhan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Sustainability is a healthy business process that includes growth, development, business continuity strategies and business development, all of which lead to the sustainability and existence of the business. Business continuity is a form of consistency of a company. This research discusses the influence of managerial ability, financial literacy and risk mitigation factors on the sustainability of MSMEs. This research is quantitative research with primary data. The research subject is the Setono Batik Wholesale Market, Pekalongan City. The sample consisted of 96 respondents selected using the incidental method, namely a sampling technique carried out by chance. Data analysis and processing was carried out using multiple regression analysis. The research results show that managerial ability and financial literacy have no effect on the sustainability of MSMEs. However, risk mitigation affects the sustainability of MSMEs.